The influence of Hellenic philosophy on the contemporary world (Cambridge Scholars Publishing, 2019)
This book consists of 21 papers on the influence of Ancient Greek philosophy on the contemporary world. It covers such areas as history, economy, art and architecture, mythology and the Riddle of Tartessus, along with an introductory essay by Professor P. Pavlopoulos, the President of the Hellenic Republic. The volume discusses a great variety of topics, including the contribution of the ancient Greek spirit to the development of contemporary western civilization, a conflict between Newton and Democritus, the side effects of natural disasters from classical Antiquity until the present day, and.